Mekanisme dan Kendala Pengelolaan Barang Bukti dan Barang Rampasan dalam Perkara Tindak Pidana Umum (Studi di Kejaksaan Negeri Manggarai Barat Provinsi Nusa Tenggara Timur) - Ngurah Agung Asteka Pradewa Artha; Ferry Anggriawan; Yusuf Eko Nahuddin (MLJ Merdeka Law Journal, 2026)
This study aims to analyze the mechanism of evidence and confiscated goods management in general criminal cases at the West Manggarai District Attorney's Office and identify the legal and sociological obstacles encountered in its implementation, using a qualitative approach through in-depth interviews. The results of the study indicate that the management of evidence and confiscated goods has in principle been implemented in accordance with Attorney General Regulation Number 7 of 2025 and Attorney General Regulation Number PER-002/A/JA/05/2017 through the stages of confiscation, recording, storage, and destruction or auction, in order to ensure security and accountability in the criminal justice process. However, legal obstacles are still found in the form of incomplete procedural arrangements and weak supervision, as well as sociological obstacles in the form of limited storage facilities and a lack of trained human resources, which impact the effectiveness of evidence management. Therefore, it is necessary to improve facilities and infrastructure, strengthen human resource capacity, optimize supervision, and adjust procedures to factual conditions in the field so that the management of evidence and confiscated goods can be carried out more efficiently, transparently, and in line with the principles of justice in the criminal justice system.